Employing Ensemble Protein-Ligand Interaction Fingerprints to Mimic Induced-Fit Theory in Structure-Based Virtual Screening Targeting Dipeptidyl Peptidase IV - Enade Perdana Istyastono; Bonifacius Ivan Wiranata; Florentinus D.O. Riswanto; Fransiska Kurniawan; Tasia Amelia; Nunung Yuniarti; Eko Adi Prasetyanto (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
We have successfully employed PyPLIF HIPPOS in retrospective Structure-Based Virtual Screening (SBVS) campaigns targeting some G-protein coupled receptors (GPCRs), which could pinpoint the molecular determinants of the protein-ligand bindings and increase the quality of the SBVS protocols. We were then tempted to append with molecular dynamics simulations using YASARA-Structure to mimic the induced-fit theory in the construction of SBVS protocols targeting dipeptidyl peptidase IV (DPP4). The protocol was retrospectively validated by employing the DPP4 ligands and decoys provided by the Directory of Useful Decoys: Enhanced (DUDE). The best SBVS protocol from this research has the balanced accuracy (BA) value of 0.836, which could be used further in prospective screening campaigns.